Effectivity of blunt end with side hole irrigation needle to eliminate root canal bacteria - Laksmiari Setyowati; Sudarjani Gunawan; Achmad Sudirman (Dental Journal (Majalah Kedokteran Gigi), 2006)
The blunt end with side hole irrigation needles have some advantages. They can be placed close to irrigation area, produce turbulent motion of irrigation material, and not push debris to apical. There is no data about the effectiveness of blunt end with side hole irrigation needle to eliminate root canal bacteria in vivo, therefore the research about effectivity of this needle compare to conventional irrigation needle was permormed. In this study 12 samples were used and divided into two groups. The conventional irrigation needle in the first group was used as control and the blunt end with side hole needle was used in the second group. The bacteriological sampling and colony counting was conducted. The paired t-test analysis before and after irrigation showed significant difference on the first and second group. The result indicated that blunt end with side hole needle more effective in eliminating root canal bacteria than conventional needle. Supporting to this study a software of fluent had been done in vitro. The result showed blunt end with side hole needle produced turbulent motion of irrigating liquid and the conventional needle produced laminar motion.